Advancements in techniques for analyzing cell permeability - da Silva, Vanderson de Jesus [UNESP]; Canales, Christian Shleider Carnero; Polinário, Giulia [UNESP]; Chesna, Vinicius Oliveira [UNESP]; Pogianeli, Rafaela Melo [UNESP]; Júnior, Edson Reinaldo [UNESP]; Venceslau, Mauro Evaristo [UNESP]; Ortoloni, Maria Fernanda [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Pavan, Fernando Rogério [UNESP] (Elsevier, 2025)
Cell permeability is a critical factor in drug development, as it directly determines the absorption and bioavailability of therapeutic compounds. This article thoroughly reviews the techniques used to analyze cell permeability, from traditional methods to innovative approaches. Initially, it delves into the characteristics, cultivation, and applications of the Caco-2 cell line, highlighting its ability to simulate the human intestinal epithelium and noting its limitations, such as the extended cultivation time required and the absence of a mucosal layer. Strategies to enhance the performance of Caco-2-based models are explored, including the use of electrospun nanofiber scaffolds and accelerated differentiation media. Additionally, alternative methods such as the Parallel Artificial Membrane Permeability Assay (PAMPA), the Madin-Darby Canine Kidney (MDCK) cell line, and the everted rat intestinal sac model are examined, evaluating their advantages and disadvantages compared to Caco-2 cells. The use of co-cultures of Caco-2 and mucin-producing HT29-MTX cells is also discussed as a more accurate replication of the human intestinal environment. The article further examines less-explored methods, such as porcine cell-based models and physiological mathematical models, offering new perspectives on the study of cell permeability. Finally, emerging three-dimensional models, including induced pluripotent stem cells, organ-on-a-chip systems, and cell spheroids, are presented, promising greater physiological relevance and improved predictability in permeability studies. This article provides a guide for researchers in selecting suitable methods for their studies, considering factors such as reproducibility, physiological relevance, cost, and cultivation time.